Efficiency of the banking sector in Indonesia, conventional and Islamic: A stochastic frontier analysis - Kamarni, Neng; Erlina, Erlina; Habbe, Abdul Hamid; Zakaria, Roza Hazli; Andrianus, Fery (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to compare the efficiency levels of conventional and Islamic banks in Indonesia and identify the main factors that influence their performance from January 2021 to June 2024. This study evaluates bank profit efficiency based on input and output variables derived from secondary data published by Bank Indonesia using the Stochastic Frontier Analysis (SFA) method. This analysis includes third-party funds, paid-in capital, placements in other banks, deposits in Bank Indonesia, and financing. The results show that conventional banks consistently demonstrate higher and more stable levels of efficiency, approaching the optimal value of 1 throughout the observation period. In contrast, Islamic banks exhibit more variability but show an increasing trend in efficiency, especially in 2024. The main performance drivers of Islamic banks include effective liquidity management through deposits and financing activities of Bank Indonesia, while paid-in capital and deposits significantly support efficiency in conventional banks. Third-party funds were found to have a negative impact on return on equity in both banking systems due to increased funding costs and operational risks. While conventional banks benefit from stable capital structures and interest-based operations, Islamic banks face structural limitations but have shown improvement in recent years. Each system has unique strengths and challenges, highlighting the need for tailored policy support to enhance efficiency and sustainability. Policymakers and regulators are encouraged to design targeted interventions to strengthen risk management, operational efficiency, and Sharia-compliant financing frameworks. For Islamic banks, optimizing third-party funds management and leveraging technology can enhance competitiveness. Meanwhile, conventional banks should integrate ethical practices to enhance long-term sustainability.